What Drives Students’ Satisfaction With E-Learning Amid COVID-19 Pandemic? - Fachrudin Fiqri Affandy; Ira Eka Pratiwi (Journal of Quality Assurance in Islamic Education (JQAIE), 2021)
This study aims to analyze the students’ satisfaction in the Faculty of Economics and Islamic Business, State Islamic Institute (IAIN) Fattahul Muluk Papua with the online learning process during the COVID-19 pandemic. It is necessary to have an evaluation of the online learning carried out during the COVID-19 pandemic so that the process can be measured and the learning quality may be improved. This study uses five Servqual dimensions, namely Tangible, Reliability, Responsiveness, Assurance, and Empathy to measure student satisfaction with the online learning process during the COVID-19 pandemic. This study uses quantitative methods with data analysis using multiple linear regression. Data were collected from 143 students of the Faculty of Economics and Islamic Business IAIN Fattahul Muluk Papua using a questionnaire that had been tested for validity and reliability. The results of this study indicate that the tangible variable and empathy variable has a significant effect on student satisfaction, while the Reliability, Responsiveness, and Assurance variables do not significantly influence students’ satisfaction with online learning during the COVID-19 pandemic.